Literasi Sertifikasi Halal dan Hambatan Implementasi Kebijakan Self-Declare pada UMKM Kuliner di Kota Pontianak - Najwa Assegaf; Midan Midan; Nur Aida; Muhammad Ridho (CV Global Research Publication, 2025)
The postponement of the mandatory halal certification requirement for Micro and Small Enterprises (MSEs) until October 2026 provides a policy adaptation window (grace period); however, the level of MSE participation, particularly in Pontianak City, remains markedly marginal. This study aims to evaluate the level of halal certification literacy, analyze psychological barriers, and identify both technical and non-technical constraints faced by culinary MSEs in Pontianak City. Employing a qualitative approach with a descriptive case study design, data were collected from five MSE actors through in-depth interviews, field observations, and document analysis. The findings reveal a pronounced disparity in literacy levels: while business actors demonstrate an adequate understanding of halal concepts from a sharia perspective, they exhibit a significant deficit in procedural literacy. Limited awareness of the Self-Declare scheme (Free Halal Certification/SEHATI) has generated psychological inhibition, manifested in apprehension toward bureaucratic complexity and perceptions of high costs. Furthermore, gaps in digital literacy related to the use of the SIHALAL application, the complexity of raw material traceability in traditional markets, and asymmetrical dissemination of information constitute the primary structural constraints. This study concludes that proactive intervention through ecosystem synergy—encompassing local government, the Halal Task Force, and academic assistance—is essential to accelerate literacy. Without comprehensive digital facilitation, MSEs are at risk of losing competitiveness and market access once the regulation is fully enforced.